Synthesis and application of Al and Sn doped TUD-1 mesoporous silica in removing methylene blue from water - Masoumeh Taherimehr; Fatemeh Lotfi; Shabnam Mehraban Khaledi; Majid Peyravi (Journal of Water and Environmental Nanotechnology)
Ensuring access to safe drinking water is a significant health issue in contemporary society. Industrial dyes, such as Methylene Blue (MB), play a substantial role in water pollution, making water unsuitable for consumption. In this research, the three-dimensional sponge-like mesoporous material TUD-1, doped with two different metals (Sn and Al) at two Si-to-metal ratios (25 and 50), was synthesized and utilized as an adsorbent for the removal of MB via the adsorption method. The adsorption data underwent analysis using the Langmuir and Freundlich isotherm models. Notably, for Sn25-TUD-1, Sn50-TUD-1, and Al50-TUD-1 adsorbents, the Langmuir model exhibited a better fit than the Freundlich model. Conversely, for Al25-TUD-1, the Freundlich model provided more accurate predictions. All adsorbents were assessed using the pseudo-second-order kinetic model. Remarkably, all prepared adsorbents effectively removed MB from water. Particularly, Sn50-TUD-1, with a remarkable BET surface area of 866 m² g⁻¹, demonstrated the highest performance with the removal capacity of 1785.6 mg g-1, at pH 7-10 and reached 1689.6 mg g-1 after five cycles of recycling. A possible mechanism for the adsorption of MB on M-TUD-1 is proposed. This research highlights the potential of TUD-1 adsorbents for efficient MB removal from wastewater.